Think together in Teology and Philosophy. A Dialogic, Itinerant, Integrative Style (Teología, 2019)
This text meditates on the fruitful links between theology and philosophy if they cultivate a dialogic, itinerant and mediating style. The Faculty of Theology of Buenos Aires is characterized by having its own faculty, made up of more than seventy philosophers and theologians who annually teach all courses. As members of a university institution they have the mission of thinking and teaching to think. As believers testify that the Christian faith is to trust thinking of God and to think trusting in God. As professors of a school of theology they are called to listen to the Logos of God that became flesh in Jesus Christ, whose love exceeds everything we can know and say. A thinking faith must have the audacity to take advantage of all the capabilities of the human logos in the integrative exercise of different complementary rationalities. The Dean of our Faculty reflects, from historical and systematic perspectives, on a sapiential intelligence centered on Christ that is jointly cultivated by both knowledge in a creative exchange. On that basis outlines a thinking, both philosophical and theological, that has the notes of a dialogical or dialogical style, a synodal or pilgrim spirit, unethos mediator or constructor. In his speech to the Faculty of Theology of Naples Francisco called to develop a theology according to the criteria proposed in his Constitution Veritatis gaudium and put the emphasis on the practice of discernment and a dialogic way of proceeding to promote a culture of mercy, the Welcome and meeting. Convergently, this article invites a thinking capable of formulating new open synthesis with hope in the Novelty of God.
Keywords: Style; Dialogue; Wisdom Intelligence; Discernment; Cloister